2012
DOI: 10.1155/2012/762918
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of the Novel Herbal Medicine, KIOM-MA, and Its Bioconversion Product, KIOM-MA128, on the Treatment of Atopic Dermatitis

Abstract: This study was conducted to determine if oral administration of the novel herbal medicine, KIOM-MA, and its Lactobacillus acidophilus-fermented product, KIOM-MA128, has therapeutic properties for the treatment of atopic dermatitis (AD). Using AD-induced BALB/c mice by Ovalbumin and aluminum hydroxide, the effectiveness of KIOM-MA and KIOM-MA128 on AD was evaluated. Oral administration of KIOM-MA and KIOM-MA128 reduced major clinical signs of AD including erythema/darkening, edema/papulation, excoriations, lich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Furthermore, our previous studies have demonstrated that KIOM-MA/MA18 have anti-inflammatory, anticancer, and antiatopic effects [1315]. In this study, we analyzed the active ingredients of KIOM-MA/MA128 via HPLC and identified the altered eleven ingredients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, our previous studies have demonstrated that KIOM-MA/MA18 have anti-inflammatory, anticancer, and antiatopic effects [1315]. In this study, we analyzed the active ingredients of KIOM-MA/MA128 via HPLC and identified the altered eleven ingredients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase was consisted of water with 0.2% acetic acid (A) and acetonitrile with 0.2% acetic acid (B). The gradient program was set as follows: 10–50% B at 0–60 min [13]. UV absorption was monitored at 203 nm and 280 nm at a flow rate of 1.0 ml/min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the KIOM-MA formula ( Glycyrrhizae Radix , Polygoni Cuspidati Rhizoma , Sophorae Flavescentis Radix , Cnidii Rhizoma , Arctii Fructus , Ginseng Radix Alba , Scrophulariae Radix , Zizyphi Semen , Angelica Gigantis Radix , and Saposhnikovia Radix ) was purchased from the Korea Medical Herbs Association (Yeongcheon, Korea), and the identification was confirmed by Porf. KiHwan Bae (The College of Pharmacy, Chungnam National University, Daejeon, Korea) [7, 11]. A total of 1.84 kg of this formula (the ratios of each constituent of KIOM-MA are shown in Table 1) was placed in 18.4 L of water and then extracted by boiling for 3 h at 115 °C.…”
Section: Methodsmentioning
confidence: 99%